Meta Analysis the Effect of Financial Distress on Good Corporate Governance Practices - Kurniawati, Dinda Dwi; Wijaya, Nurhayat Rokhmat; Hwihanus,; Ratnawati, Tri (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Financial distress is a condition of unhealthy company financial performance due to financial difficulties. To avoid financial distress, companies implement good corporate governance practices, known as Good Corporate Governance (GCG). The purpose of this study is to examine the role of financial distress in the context of good corporate governance, based on the observed phenomenon. This research was conducted using a meta-analysis method from previous research using 24 journals with different types of business sectors that examined the effect of financial distress on good corporate governance. The results showed that the mechanism of good corporate governance through the proxy of the audit committee, managerial ownership, number of commissioners, number of directors, leverage, cash flow, and sales growth, has a significant relationship with financial distress. However, the results of good corporate governance through proxies. liquidity, institutional ownership, and the proportion of commissioners. independent related insignificantly. Other results also show that financial distress can be predicted by good corporate governance mechanisms through financial ratio analysis and macroeconomic factor analysis.